2023
DOI: 10.1039/d3gc01055d
|View full text |Cite
|
Sign up to set email alerts
|

Expanding lignin thermal property space by fractionation and covalent modification

Abstract: To fully exploit kraft lignin’s potential in material applications, we need to achieve tight control over those key physicochemical lignin parameters that ultimately determine, and serve as proxy for, the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Such modified lignins would therefore not adhere to the FF (or similar) relationship and require an alternative method for T g prediction. Previously we showed that fractionation and systematic (partial) modification of a Stora Enso's Lineo Classic softwood kraft lignin (SEKL) yielded a set of lignin samples with a very large (and tuneable) range of T g s. More specifically, solvent fractionation using a gradient of EtOAc, EtOH, MeOH and acetone gave five specific fractions (including the final insoluble residual fraction) [9] . These lignins were well partitioned by molecular weight, with a T g thermal property space range of 152 °C.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Such modified lignins would therefore not adhere to the FF (or similar) relationship and require an alternative method for T g prediction. Previously we showed that fractionation and systematic (partial) modification of a Stora Enso's Lineo Classic softwood kraft lignin (SEKL) yielded a set of lignin samples with a very large (and tuneable) range of T g s. More specifically, solvent fractionation using a gradient of EtOAc, EtOH, MeOH and acetone gave five specific fractions (including the final insoluble residual fraction) [9] . These lignins were well partitioned by molecular weight, with a T g thermal property space range of 152 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Previously we showed that fractionation and systematic (partial) modification of a Stora Enso's Lineo Classic softwood kraft lignin (SEKL) yielded a set of lignin samples with a very large (and tuneable) range of T g s. More specifically, solvent fractionation using a gradient of EtOAc, EtOH, MeOH and acetone gave five specific fractions (including the final insoluble residual fraction). [9] These lignins were well partitioned by molecular weight, with a T g thermal property space range of 152 °C. Subsequent allylation generated a library of unique samples of lower T g (relative to the parent fraction), thus expanding upon this property space to a range of 213 °C, from 12 to 225 °C.…”
Section: Prediction Of T G For Derivatised Ligninsmentioning
confidence: 99%
See 2 more Smart Citations
“…kraft, soda, and organosolv), different degradation pathways occur, meaning that each fractionation method leads to process-specific linkages and fragmentation patterns . These unintended modifications of the technical lignin structure further contribute to the structural heterogeneity, and the recalcitrant C–C linkages leave these lignins less suited for depolymerization strategies. ,, Consequently, more C atom economic approaches for utilizing technical lignins hinge on the application of lignin fractionation, , modification, or a combination of both , to achieve suitably homogeneous samples for lignin-to-materials applications. While deep depolymerization of technical lignins may seem an attractive potential approach toward monoaromatics, its recalcitrance and complexity again hamper these efforts, limiting its efficiency and resulting in complex mixtures of products …”
Section: Introductionmentioning
confidence: 99%